2015
DOI: 10.1097/ijg.0000000000000215
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Selective Laser Trabeculoplasty Energy for Maximal Intraocular Pressure Reduction in Open-Angle Glaucoma

Abstract: A higher SLT energy, in the range of 214.6 to 234.9 mJ, seems to be associated with an improved IOP-lowering response. Further randomized control trials with treatment stratification are needed to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 20 publications
1
23
1
3
Order By: Relevance
“…26 For SLT, delivering a higher total energy has been demonstrated to increase the amount of IOP reduction with no permanent changes to the cornea. 27,28 In MLT, no such evidence exists on the optimal number of laser shots but Ahmed et al reported that at 4 months postlaser, the greatest IOP reduction was achieved when using an energy of 1000 mW per shot as compared to 300 mW or 700 mW. 29 This formed the basis of our treatment protocol in delivering a mean of 1000 mW per shot in each patient.…”
Section: Discussionmentioning
confidence: 97%
“…26 For SLT, delivering a higher total energy has been demonstrated to increase the amount of IOP reduction with no permanent changes to the cornea. 27,28 In MLT, no such evidence exists on the optimal number of laser shots but Ahmed et al reported that at 4 months postlaser, the greatest IOP reduction was achieved when using an energy of 1000 mW per shot as compared to 300 mW or 700 mW. 29 This formed the basis of our treatment protocol in delivering a mean of 1000 mW per shot in each patient.…”
Section: Discussionmentioning
confidence: 97%
“…The average IOP reduction at 1 month following SLT was 20.2 ± 14.6%. A total energy level of 226.1 mJ (95% confidence interval: 214.58–234.87 mJ) was found to result in a significant reduction in IOP greater than 25% [28]. Results from this study suggest that a total SLT energy level in the range of 214.6–234.9 mJ may lead to higher success rates.…”
Section: Surgical Techniquementioning
confidence: 94%
“…The energy level employed in SLT therapy may also be an important prognostic factor [28]. Age, gender, race, central corneal thickness, history of ALT, history of cataract surgery, and standard automated perimetry mean deviation were not found to be associated with greater IOP reduction after SLT [2527].…”
Section: Prognostic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies found a positive correlation between these factors and success rates, others did not. Regarding laser parameters itself, although good results have been recently reported with low power SLT (0.4 mJ per shot; repeated annually) (19) , most studies have suggested better outcomes with higher power settings (energy per shot), more extensive laser treatment (360 degree), and greater number of shots (18,25,65,66) . There is also a strong correlation between SLT outcomes when we consider both eyes from the same patient (67) .…”
Section: Success Predictors Of Selective Laser Trabeculoplastymentioning
confidence: 99%